Heat evolution of alkali-activated materials: A review on influence factors. (3rd January 2022) - Mohamed, Rosnita; Abd Razak, Rafiza; Abdullah, Mohd Mustafa Al Bakri; Abd Rahim, Shayfull Zamree Abd; Yuan-Li, Long; Subaer,; Sandu, Andrei Victor; Wysłocki, Jerzy J.
Highlights: Heat evolution is significant in understanding the alkali activation process. Calorimetric data enables the interpretation of reaction kinetics of alkali activation. Factors affecting alkali activation process which lead to variations of heat evolution. Potential of heat evolution in understanding the ambient-curing/self-curing AAMs. Potential of self-curing AAMs for on-site application as alternatives to the OPC. Abstract: The usage of ordinary Portland cement (OPC) in construction has become a great concern among researchers due to the carbon dioxide (CO2 ) emission during production. As alternatives, alkali-activated materials (AAMs), which include geopolymers, have been introduced as green material due to their similar properties to OPC and minimal CO2 emission. This review highlights the heat evolution during alkali activation, which has been proven to be a reliable technique for providing information on the cumulative heat evolution and kinetic parameters, encompassing reaction rates, mechanism, and activation energy. The factors influencing heat evolution such as effect of materials used and parameters of mix design, including alkali solution concentration, alkali-activator ratios and solid-to-liquid ratios/liquid-to-solid ratios are briefly reviewed to highlight the significance of heat evolution in understanding the alkali activation process for the formation of AAMs.